Standardized Psychosocial Assessment Before Left Ventricular Assist Device Implantation: An Important Predictive Measure. (January 2019) - Sperry, Brett W.; Ikram, Asad; Alvarez, Paulino A.; Perez, Antonio L.; Kendall, Kay; Gorodeski, Eiran Z.; Starling, Randall C.
Abstract : Background: Before consideration of advanced cardiac therapies, guidelines recommend a comprehensive multidisciplinary examination, including psychosocial assessment. The Stanford Integrated Psychosocial Assessment for Transplantation (SIPAT) has emerged as a highly reproducible tool to assess for psychosocial impairment and is associated with negative medical and psychosocial outcomes after transplantation. We sought to assess the association between SIPAT and outcomes after left ventricular assist device. Methods and Results: We evaluated 128 patients implanted with a first left ventricular assist device at the Cleveland Clinic from 2013 to 2017 who underwent a prospectively collected quantitative psychosocial assessment using SIPAT. Several survival analyses were performed testing the association between SIPAT score and mortality, first adverse event (defined as hospitalization, device exchange, or death), and recurring adverse events after multivariable adjustment. Median SIPAT score was 14 (interquartile range, 9.5–22.5), with higher values (representing more impairment) seen in patients implanted as destination therapy. After a median follow-up of 349 (interquartile range, 178–684) days, there were 319 adverse events (18 deaths, 10 device exchanges, and 291 readmissions) with 2.5±2.4 events per patient. Higher preimplant SIPAT scores were not associated with mortality ( P =0.764) or time to a first adverse event ( P =0.589) but were associated with cumulative adverse events (hazard ratio, 1.31; 95% CI, 1.09–1.58; P =0.005 per Δ10 in score). In addition, SIPAT was associated with days alive outside of the hospital ( P =0.016). Conclusions: A standardized assessment of psychosocial impairment after left ventricular assist device using the SIPAT score was not associated with mortality or time to first adverse event but was associated with cumulative adverse cardiac events. This score may provide insight when structuring mitigation strategies for high-risk patients and should be further tested in a prospective multicenter study. Abstract : Supplemental Digital Content is available in the text.